A new concept of white light generation using a nano-waveguide for the solar radiation collection use - Yupapin, P. P.; Pornsuwancharoen, N.; Sakulpong, R.; Plangklang, B. (My University, 2010)
We propose a novel system of a nano-waveguide that can be used to generate the continuous optical spectrum, i.e. white light. A system consists of two micro-ring resonators and a nano-ring resonator that can be integrated into a single system. The large bandwidth signal is generated using a soliton pulse propagating within a Kerr-type nonlinear medium, whereas the continuous bandwidth or wavelength of light signal can be performed. Results obtained have shown the potential of using such a system for white light source generation and amplification, which is discussed. The amplified pulse can be stored within a nano-waveguide, which is allowed to form the continuous spectrum after amplification. Alternatively, the low-level solar radiation can be amplified, and the bandwidth signals can also be enlarged. © 2009 Elsevier GmbH.
Keywords: Continuous spectra; Nano-waveguide; Solar radiation collection; White light